2022
DOI: 10.1038/s41467-022-29066-1
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord injury impairs cardiac function due to impaired bulbospinal sympathetic control

Abstract: Spinal cord injury chronically alters cardiac structure and function and is associated with increased odds for cardiovascular disease. Here, we investigate the cardiac consequences of spinal cord injury on the acute-to-chronic continuum, and the contribution of altered bulbospinal sympathetic control to the decline in cardiac function following spinal cord injury. By combining experimental rat models of spinal cord injury with prospective clinical studies, we demonstrate that spinal cord injury causes a rapid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 73 publications
1
11
0
Order By: Relevance
“…In this study, CIHH was found to promote bone formation and prevent deterioration of trabecular bone at femur and tibia in SCI rat. Moreover, there are other complications including chronic liver pathology ( 21 ), vascular dysfunction ( 22 ), ventricular arrhythmias ( 23 ), and dysfunction of cardiac ( 24 ), respiratory ( 25 ), and nervous systems ( 26 ). Unfortunately, the role of CIHH on these complications is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, CIHH was found to promote bone formation and prevent deterioration of trabecular bone at femur and tibia in SCI rat. Moreover, there are other complications including chronic liver pathology ( 21 ), vascular dysfunction ( 22 ), ventricular arrhythmias ( 23 ), and dysfunction of cardiac ( 24 ), respiratory ( 25 ), and nervous systems ( 26 ). Unfortunately, the role of CIHH on these complications is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…As the LTPA measures were highly variable but somewhat comparable amongst the cervical SCI and thoracolumbar SCI participants, the most likely explanation for the differences between groups can be attributed to the disrupted supraspinal regulation of sympathetic activity to the heart following cervical SCI ( 5 ). To support this, our group has previously published translational work suggesting the mechanism behind the reduction in cardiac function is underpinned by interrupted bulbospinal sympathetic control ( 27 ). Conversely, cardiac sympathetic control is preserved in those with thoracolumbar SCI.…”
Section: Discussionmentioning
confidence: 99%
“…T2−3) are sufficient to cause a marked decrement in cardiac contractile function, evidenced by a significant reduction in E es in both rodent and porcine models (Fossey et al., 2022; Poormasjedi‐Meibod et al., 2019; Squair et al., 2018; Wainman et al., 2021; Williams et al., 2020). Moreover, in a recent manuscript, describing a series of experiments in both rodents and individuals with SCI, we reported that SCI induces considerable contractile dysfunction post‐injury that occurs due to the loss of bulbospinal sympathetic control over the heart (Fossey et al., 2022). Terminal in vivo cardiovascular function assessment (i.e.…”
Section: Methodsmentioning
confidence: 99%